2008
DOI: 10.4049/jimmunol.181.1.521
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Apoptotic Bcl-2 Family Member Mcl-1 Promotes T Lymphocyte Survival at Multiple Stages

Abstract: T lymphocyte development and function are tightly regulated by the intrinsic death pathway through members of the Bcl-2 family. Genetic studies have demonstrated that the Bcl-2 family member Mcl-1 is an important anti-apoptotic protein in the development of multiple cell types including T lymphocytes. However, the expression pattern and anti-apoptotic roles of Mcl-1 in T lymphocytes at different developmental stages remain to be fully determined. In this study, we examined the expression pattern of Mcl-1 in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
150
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 40 publications
17
150
0
Order By: Relevance
“…2C). This finding is consistent with the reports demonstrating the redundant role of Mcl1 and Bclx L in antiapoptotic function (30,38).…”
Section: Tak1-jnk Axis Regulates Mcl1 Stabilitysupporting
confidence: 83%
See 2 more Smart Citations
“…2C). This finding is consistent with the reports demonstrating the redundant role of Mcl1 and Bclx L in antiapoptotic function (30,38).…”
Section: Tak1-jnk Axis Regulates Mcl1 Stabilitysupporting
confidence: 83%
“…2D and data not shown). Instead, we found that JNK activity correlates well with phosphorylation status and stability of Mcl1, an antiapoptotic protein expressed in activated T cells (29)(30)(31)(32). We concluded that the IL-2R-mediated TAK1-JNK axis regulates the survival of activated T cells through stabilization of Mcl1, although its molecular mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Mcl-1 is expressed at comparable levels in all of these cell subsets. 11 Bim is the BH3-only protein most critical for thymocyte deletion: thymocytes lacking Bim were refractory to apoptosis induced by stimulation with CD3 antibodies and Bim deficiency in transgenic (tg) mice expressing autoreactive TCRs severely impaired thymocyte apoptosis. 12,13 Studies using tg mice showed that overexpression of Bcl-2 [13][14][15][16] or Bcl-x L 8 enhanced the survival of thymocytes (and mature T cells) exposed to diverse cellular stresses.…”
mentioning
confidence: 99%
“…However, little is actually understood about mechanisms that suppress or enforce cell death downstream of the pre-TCR but the balance of pro-apoptotic and anti-apoptotic Bcl-2 family members appears to play a significant role during β-selection [86,95,103,104]. In particular, repression of Bid and Bim expression has recently been reported to be important for survival during β-selection [95] and Bcl2A1 expression is increased during β-selection [86].…”
Section: Death Of C-myb Deficient Pre-tcr+ Thymocytes Is Independent mentioning
confidence: 99%